Originally Posted by

**bugatti79** Folks,

I am struggling with this seemingly simple task of solving for s and t in terms of x and y to ultimately get u in terms of x and y.

$\displaystyle x=s+st/4+t^2/4$ (1)

$\displaystyle y=s+t$ (2)

$\displaystyle u=s/4+t/2$ (3)

My attempt is as follows: From eqn 1 find t, its a quadratic in t

$\displaystyle t=\frac{-s+- \sqrt {s^2+4(4x-4s)}}{2}$ (4)

From (2) find t $\displaystyle t=y-s$ (5)

Then equate 4 and 5???.... Im actually lost....

The answers are

$\displaystyle s=\frac{4x-y^2}{4-y}$

$\displaystyle t=\frac{4(y-x)}{4-y}$

$\displaystyle u=\frac{8y-4x-y^2}{4(4-y)}$